A Traumatic Analysis of the First-level Witnessing Effective Enlistment in Bennett and Komunyakaa's Poems - SeyedehYasaman Ghodsi; Narges Montakhabi Bakhtvar; Razieh Eslamieh (Critical Literary Studies)
The present essay focuses on the witnessing process of the enlisting poets’ effective responsiveness to the devastations they encountered; the two poets to be studied have been directly or indirectly traumatized by wars. The analytical perspective draws on Dominick LaCapra’s theories on historical trauma. It intends to uncover the traumatic effects of circumstances in post-war poems. The methodological procedure is grounded in the qualitative appraisal of the emotive aspect of the poets’ expressionist representation through critical discourse analysis. Trauma theories influence the research approach in historical and structural science, emphasizing witnessing levels, coined by Dori Laub, as the most significant determinant of the gestalt of interpretations. The poems’ demolished vibe exploits an insight into the amalgamation of historical trauma and its steps towards salvation. The authorial intentionality in war poetry aspires to enlighten human sorrow and redemption by restoring the literary application of the historical, structural, and perpetrator trauma hypothesis. The melioristic agenda for edification via physical and critical phases, such as acting out and working through, coined by LaCapra, foci in the varied poems to be scrutinized, enables the poets’ to maintain their readers’ empathetic identification with their characters’ predicaments in a psychoanalytic context.